Outcomes of Muscle Reinnervation with Direct Nerve Implantation into the Native Motor Zone of the Target Muscle - Sobotka, Stanislaw; Chen, Jingming; Nyirenda, Themba; Mu, Liancai (Journal of Reconstructive Microsurgery, 2017)
Background Our recent work has demonstrated that the native motor zone (NMZ) within a given skeletal muscle is the best site for muscle reinnervation. This study was designed to explore the outcomes of direct nerve implantation (DNI) into the NMZ of denervated sternomastoid (SM) muscle in a rat model.Methods The right SM muscle was experimentally denervated by transecting its innervating nerve. The proximal stump of the severed SM nerve was immediately implanted into a small muscle slit made in the NMZ of the muscle where denervated motor endplates were concentrated. The outcomes of DNI-NMZ reinnervation were evaluated 3 months after surgery. Specifically, the degree of functional recovery was examined with muscle force measurement. The extent of nerve regeneration and endplate reinnervation was assessed using histological and immunohistochemical methods.Results This study showed that the mean muscle force of the treated muscles was 64% of the contralateral control. Reinnervated SM muscles weighed 71% of the weight of the control muscles. Abundant regenerated axons were identified in the NMZ of the target muscle. The mean number and area of the regenerated axons in the treated muscles was computed to be 62% and 51% of the control muscles, respectively. On average, 66% of the denervated endplates in the treated muscles were reinnervated by regenerated axons.Conclusion Our results suggest that the NMZ within a muscle is an ideal site for endplate reinnervation and satisfactory functional recovery. Further studies are needed to promote the efficacy of DNI-NMZ technique for muscle reinnervation.
Keywords: direct nerve implantation; nerve regeneration; muscle force measurement